Fishmeal alternative from renewable CO2 for rainbow trout feed. (7th July 2020) - Lee, Seunghan; Kumar, Vikas; Cleveland, Beth; Romano, Nicholas; Vemuri, Goutham N; Yadav, Amit K.; Meiler, Kristen; Hardy, Ronald W.
Abstract: The rapid global growth in fish farming and limited supply of fish meal (FM) has consequently reduced FM inclusion levels in compound feeds leading to a higher reliance on alternative protein sources. Sasya is a single cell protein (SCP) product that has a similar amino acid profile as FM. The aim of this study was to evaluate the effects of replacing FM with SCP on in vivo digestibility, growth, feed efficiency, whole‐body proximate/amino acid composition and gene expression levels of various hepatic enzymes in rainbow trout ( Oncorhynchus mykiss ). Three isonitrogenous (470 g/kg crude protein) and isolipidic (18 g/kg crude lipid) diets were formulated as follows: Diet 1: control (30% FM); Diet 2: 24% FM + 6% SCP and Diet 3 :18% FM + 12% SCP. Each diet was hand‐fed to triplicate tanks containing 30 rainbow trout fingerlings (4.99 ± 0.20 g) for 9 weeks. Apparent digestibility coefficients of SCP for dry matter, crude protein, lipid and energy were 60, 80, 93 and 74% respectively. Growth performance (final weight: 69–71 g), feed conversion ratios (0.91–0.94) as well as whole‐body protein and amino acid composition were unaffected by diets. However, Diet 3 significantly increased whole‐body crude fat and energy. Fish fed the SCP‐based diets had significantly higher expression for carnitine palmitoyltransferase‐1b (CPT1b), fatty acid delta 6 desaturase (FADS6) and fatty acid elongase 5 compared to the control. Overall, the quality of the SCP was similar as FM. Therefore, this product could enlarge the portfolio of alternative protein sources that can be used in fish diets and thus open a new market opportunity for use of a new feed resource in the feed industry.